Correlative analysis from a phase I clinical trial of intrapleural administration of oncolytic vaccinia virus (Olvi-vec) in patients with malignant pleural mesothelioma - Chintala, Navin K.; Choe, Jennie K.; McGee, Erin; Bellis, Rebecca; Saini, Jasmeen K.; Banerjee, Srijita; Moreira, Andre L.; Zauderer, Marjorie G.; Adusumilli, Prasad S.; Rusch, Valerie W. (Frontiers in Immunology, 2023)
Background: The attenuated, genetically engineered vaccinia virus has been shown to be a promising oncolytic virus for the treatment of patients with solid tumors, through both direct cytotoxic and immune-activating effects. Whereas systemically administered oncolytic viruses can be neutralized by pre-existing antibodies, locoregionally administered viruses can infect tumor cells and generate immune responses. We conducted a phase I clinical trial to investigate the safety, feasibility and immune activating effects of intrapleural administration of oncolytic vaccinia virus (NCT01766739). Methods: Eighteen patients with malignant pleural effusion due to either malignant pleural mesothelioma or metastatic disease (non-small cell lung cancer or breast cancer) underwent intrapleural administration of the oncolytic vaccinia virus using a dose-escalating method, following drainage of malignant pleural effusion. The primary objective of this trial was to determine a recommended dose of attenuated vaccinia virus. The secondary objectives were to assess feasibility, safety and tolerability; evaluate viral presence in the tumor and serum as well as viral shedding in pleural fluid, sputum, and urine; and evaluate anti-vaccinia virus immune response. Correlative analyses were performed on body fluids, peripheral blood, and tumor specimens obtained from pre- and post-treatment timepoints. Results: Treatment with attenuated vaccinia virus at the dose of 1.00E+07 plaque-forming units (PFU) to 6.00E+09 PFU was feasible and safe, with no treatment-associated mortalities or dose-limiting toxicities. Vaccinia virus was detectable in tumor cells 2-5 days post-treatment, and treatment was associated with a decrease in tumor cell density and an increase in immune cell density as assessed by a pathologist blinded to the clinical observations. An increase in both effector (CD8+, NK, cytotoxic cells) and suppressor (Tregs) immune cell populations was observed following treatment. Dendritic cell and neutrophil populations were also increased, and immune effector and immune checkpoint proteins (IFN-γ, granzyme B, perforin, PD-1, TGFβ1, PD-L1, and PD-L2) and cytokines (IFN-γ, TNF-α and RANTES) were upregulated. Conclusion: The intrapleural administration of oncolytic vaccinia viral therapy is safe and feasible and generates regional immune response without overt systemic symptoms. Clinical Trial Registration: https://clinicaltrials.gov/ct2/show/NCT01766739, identifier NCT01766739